Involvement of Ras GTPase-activating protein SH3 domain-binding protein 1 in the epithelial-to-mesenchymal transition-induced metastasis of breast cancer cells via the Smad signaling pathway - Hao Zhang; Yan Ma; Shenghua Zhang; Hong Liu; Hongwei He; Naren Li; Yuyan Gong; Shuangshuang Zhao; Jian–Dong Jiang; Rong‐Guang Shao (2015)
// Hao Zhang 1, * , Yan Ma 1, * , Shenghua Zhang 1 , Hong Liu 1 , Hongwei He 1 , Naren Li 1 , Yuyan Gong 1 , Shuangshuang Zhao 1 , Jian-dong Jiang 2, 3 , Rong-guang Shao 1 1 Department of Oncology, Institute of Medicinal Biotechnology, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, China 2 Institute of Medicinal Biotechnology, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, China 3 State Key Laboratory of Bioactive Substances and Functions of Natural Medicines, Institute of Materia Medica, Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, China * These authors have contributed equally to this work Correspondence to: Rong-guang Shao, e-mail: shaor@imb.pumc.edu.cn Keywords: G3BP1, EMT, breast cancer, Smad signaling pathway Received: November 27, 2014      Accepted: April 09, 2015      Published: April 20, 2015 ABSTRACT In situ models of epithelial-to-mesenchymal transition (EMT)-induced carcinoma develop into metastatic carcinoma, which is associated with drug resistance and disease recurrence in human breast cancer. Ras G TPase-activating protein SH 3 domain- b inding p rotein 1 (G3BP1), an essential Ras mediator, has been implicated in cancer development, including cell growth, motility, invasion and apoptosis. Here, we demonstrated that the upregulation of G3BP1 activates the EMT in breast cancer cells. Silencing Smads almost completely blocked this G3BP1-induced EMT, suggesting that this process depends on the Smad signaling pathway. We also found that G3BP1 interacted with the Smad complex. Based on these results, we proposed that G3BP1 might act as a novel co-factor of Smads by regulating their phosphorylation status. Moreover, knockdown of G3BP1 suppressed the mesenchymal phenotype of MDA-MB-231 cells in vitro and suppressed tumor growth and lung metastasis of 4T1 cells in vivo . Our findings identified a novel function of G3BP1 in the progression of breast cancer via activation of the EMT, indicating that G3BP1 might represent a potential therapeutic target for metastatic human breast cancer.